POTENSI PEMANFAATAN KITOSAN TERMODIFIKASI ASAP CAIR SEBAGAI BAHAN EDIBLE COATING ANTI MIKROBA UNTUK PENGAWETAN DAGING - M. Hanafiah,; M. Faisal; Izarul Machdar (Talenta Publisher (Universitas Sumatera Utara), 2018)
This research is a preliminary study of the utilization of chitosan modified with liquid smoke to produce edible coating material that can be used as a preservative of beef. Chitosan compounds obtained from shrimp shell waste, while liquid smoke produced from pyrolysis of palm shells at a temperature of 340oC. Edible coating solution with various concentrations was made by dissolving chitosan (1-1.5%) into 3% liquid smoke, which was then applied as a meat preservative. Meat samples that have been dipped edible coating for 15 minutes, then stored in the refrigerator and observed decreased endurance every 24 hours for 8 days. Analysis results of Gas Chromatography-Mass Spectrometry (GC-MS) showed that liquid smoke contains phenol and acetic acid compounds that have antimocrobial properties. Meat endurance test was done by analyzing the aroma, texture and color of meat. The results showed that the beef that has been coated liquid chitosan solution can last up to 7 days. Chitosan concentration affects the endurance of meat, the greater the chitosan concentration, the better the meat endurance. The optimum concentration was obtained at 1% of chitosan, the meat still has an acceptable aroma, texture and color for up to 6 days. This suggests that chitosan-liquid smoke can be used as an edible coating material.